MODEL HIDRODINAMIKA BIOREAKTOR TANAMAN : KONSEP PERMEABILITAS - Mubiar Purwasasmita; Khoirul Hadi (Reaktor, 2015)
Abstract HYDRODYNAMIC MODEL OF THE PLANT BIOREACTOR (THE PERMEABILITY CONCEPT). Water flow is important in transport of plant nutrients. To accomadate water flow in plant bioreactor, it is necesary enough space by adding compost, i.e. material from plant residue which contains many of capillary tube. Many hydrodynamic models of water flow in porous and capillary medium are proposed, but there is no the specific model for plant bioreactor which contains particle beads and capillary tube. There are three models are proposed in this study, one each other are different in complexity. The first model has four parameters with mean error of 0.457, the second one has five parameters with error of 0.464, and the last one has seven parameters with mean error of 0.574. From the models, it is found that increasing in particle size or compost fraction will result in increasing permeability. With the compost to bed volume ratio of 1:4, the permeability increase significantly compared to the soil and sandstone. By taking into account of the permeability value in the governing equation of single cyllindrical root system, the water flow is not a rate limiting step for a long of the root. In order to ensure the existence of water flow in the bioreactor, it is suggested to use compost to bed volume ration of 1:1. Keywords: flow in capillary-porous media; permeability; root water uptake;the plant bioreactor Abstrak Aliran air dalam bioreaktor sangat penting dalam perpindahan nutrisi tanaman. Untuk memfasilitasi aliran air dalam bioreaktor tanaman, diperlukan rekayasa ruang melalui penambahan kompos, berupa material bekas tanaman yang mengandung pipa-pipa kapiler. Sudah tersedia berbagai model hidrodinamika untuk aliran lambat melewati unggun, namun belum ada yang secara khusus untuk bioreaktor tanaman yang memiliki butiran partikel dan potongan pipa kapiler. Pada kajian ini terdapat tiga model aliran yang ditinjau, masing-masing hanya berbeda dari sisi kompleksitasnya. Model pertama memiliki empat parameter dengan kesalahan rata-rata 0,457, model kedua memiliki lima parameter dengan kesalahan rata-rata 0,464, dan model ketiga dengan tujuh parameter dengan kesalahan rata-rata 0,574. Dengan menggunakan model tersebut diperoleh bahwa permeabilitas akan meningkat seiring dengan bertambahnya ukuran partikel dan atau fraksi kompos. Penambahan kompos seperempat dari volume unggun total akan memberikan peningkatan permeabilitas yang signifikan dibandingkan dengan tanah dan batuan pasir biasa. Dengan memasukkan parameter ini kedalam persamaan pengambilan air pada sistem akar silinder tunggal, maka perpindahan air bukan lagi menjadi tahap pembatas laju di sepanjang akar. Untuk menjamin ketersediaan aliran, disarankan menggunakan kompos sebesar setengah dari volume unggun total.